De primeira viagem: significados e vivências da paternidade para pais de diferentes gerações - Gabriela Teixeira Vieira (2011)
Since the 80's there has been a major concern in academic context in approaching men's participation in domestic life and these studies have been expanding in Brazil and other countries. Nowadays researches seek to listen directly fathers, in order to comprehend their experiences, feelings and practices and, through research with other actors involved with the theme, how the society promotes or difficult the exercise of parenting in everyday life. Under the hypothesis that the meanings and experiences of parenting are presented in different ways for different generations, the present study aimed to describe and analyze how men of different generations understand and experience the birth of first child and integrate aspects of paternity in their identity. For this purpose, 14 man aged between 20 and 50 years were interviewed, all parents of their first child, aged 2 to 7 months. All of them lived with their child's mother (wife/partner), in the metropolitan area of Belo Horizonte/MG. Semi-structured interviews were conducted and transcribed. The collected information was submitted to Thematic Content Analysis, with the support of a software, NVivo 7. The results were analyzed based on the Social Identity Theory of Henri Tajfel and on fatherhoods studies developed in recent decades. The central definition of fatherhood, analyzing all the results, seems to be "be responsible", which runs through the discourse of parents at many moments in the interviews. Other meanings, based on models that range from traditional to recent notions are linked to this definition. Thus, respondents generally consider that being a parent is an act of responsibility, for education/child rearing, for providing economic support, care and protection. They also consider that a good father is someone who "give love and affection" and "is present". It is also based on the notion of responsibility that the respondents differ themselves from those who are not parents and emphasize aspects in their discourse that put them in a higher level compared with other parents, in regard to responsibility, affection and presence. Social changes do not emerge as a way of replacing the old values by new ones, but there is an addition of new values and the old ones can be reframed. Coexist in our society different models and practices, aligned with traditional and recent values and meanings. The analysis of the collected information shows that although there is a sharing of the meanings of fatherhood, the generational factor is directly related to the variation in daily activities directed at their son/daughter, without having, however, a greater degree of participation directly linked to the younger age of fathers. Parents aged between 30 and 39 were more participative, engaged in a wider range of activities and more satisfied than the younger ones, which may be considered related to the fact that they were born and lived his youth at a time when equality values were emerging and spreading through the society. Besides that, working conditions of the interviewed fathers and their wives/partners, plans about the pregnancy and personal and social expectations seems to influence significatively the experience of fatherhood at different ages.